2000
DOI: 10.1073/pnas.140220397
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of action of a pestivirus antiviral compound

Abstract: We report here the discovery of a small molecule inhibitor of pestivirus replication. The compound, designated VP32947, inhibits the replication of bovine viral diarrhea virus (BVDV) in cell culture at a 50% inhibitory concentration of approximately 20 nM. VP32947 inhibits both cytopathic and noncytopathic pestiviruses, including isolates of BVDV-1, BVDV-2, border disease virus, and classical swine fever virus. However, the compound shows no activity against viruses from unrelated virus groups. Time of drug ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
65
1
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(69 citation statements)
references
References 22 publications
1
65
1
2
Order By: Relevance
“…In the absence of a reliable cell culture system able to support hepatitis C virus (HCV) replication and based on the degree of homology in terms of genomic organization, replication strategy (including chronicity), and protein function (25), BVDV has been proposed as a surrogate model to study the action of antiviral molecules (2,29). We have previously shown that the BVDV envelope glycoproteins E1, E2, and the E2 precursor E2-p7 interact with calnexin and that this interaction can be inhibited using the iminosugar derivative Nbutyl-DNJ (NB-DNJ) (5).…”
mentioning
confidence: 99%
“…In the absence of a reliable cell culture system able to support hepatitis C virus (HCV) replication and based on the degree of homology in terms of genomic organization, replication strategy (including chronicity), and protein function (25), BVDV has been proposed as a surrogate model to study the action of antiviral molecules (2,29). We have previously shown that the BVDV envelope glycoproteins E1, E2, and the E2 precursor E2-p7 interact with calnexin and that this interaction can be inhibited using the iminosugar derivative Nbutyl-DNJ (NB-DNJ) (5).…”
mentioning
confidence: 99%
“…In the absence of an efficient cell culture system able to support hepatitis C virus (HCV) replication, BVDV has been adopted as a model and surrogate for HCV (1), as both viruses share molecular and virological features. HCV and BVDV are small, enveloped viruses with positive single-stranded RNA genomes of approximately 9,600 and 12,600 nucleotides, respectively.…”
mentioning
confidence: 99%
“…The C-terminal NS3 domain encodes an RNA helicase that is required for an unknown step(s) in RNA replication (16,17,51). NS5B, the viral RNAdependent RNA polymerase, has been expressed, purified, and extensively compared to the corresponding enzyme of HCV (1,24,57). Essentially nothing is known about the functions of p7, NS2, NS4B, or NS5A, although NS5A has been shown to be a serine phosphoprotein that is tightly associated with one or more cellular kinases (37).…”
mentioning
confidence: 99%